407. A STUDY OF OUTCOMES OF ESOPHAGEAL CANCER SURGERY FOR ELDERLY PATIENTS OVER 80 YEARS OF AGE. (24th September 2022) - Shigeno, Takashi; Fujita, Takeo; Kajiyama, Daisuke; Sato, Kazuma; Fujiwara, Naoto; Daiko, Hiroyuki
Abstract: According to the 2020 edition of the situation in Japan, the population aged 65 and over reached 35.89 million, accounting for 28.4% of the total population. Esophageal cancer is a common disease among the elderly, and it is expected that the number of encounters with elderly esophageal cancer patients will increase further in the future. We examined the outcomes of esophageal cancer surgery for elderly patients at our hospital. Of 769 thoracic esophageal cancer resections performed at our hospital from 2015–2019, 53 (6.8%) patients aged 80 years or older were included. The mean age was 82 (80–94) years, the male/female ratio was 45/8, tumor localization was Ut/Mt/Lt 5/23/25, and cStage (UICC 7th edition) was I/II/III/IV 12/8/30/3. The surgical technique was 1-stage resection/2-stage segmental resection/mediastinoscopy in 9/32/12 cases. Surgical complications were suture failure, recurrent nerve palsy, and pulmonary complications in 2/12/11 patients. The 3-year survival rate was 66.7%, and the 3-year recurrence-free survival rate was 62.1%. The 3-year survival rate was 66.7% and the 3-year recurrence-free survival rate was 62.1%. Esophageal cancer surgery may be a treatment option for elderly patients who are able to tolerate surgery, even if they are over 80 years of age. Our hospital provides a multidisciplinary team intervention for patients over 70 years of age 3–4 weeks prior to surgery, during the perioperative period, and after discharge, which may be useful in reducing postoperative complications.